Institutional Management at KB Bunayya Islamic Center Bin Baz: (KB Bunayya Icbb) - Rahmawati, Sarah; Gusmian, Islah; Giyoto, Giyoto (Jurnal Edusci, 2025)
Background. Education is one of the efforts to improve the quality of human life by developing human potential. Education is not a simple activity but a dynamic activity. Aims. This study aims to investigate the institutional management at KB Bunayya ICBB. This article examines institutional management at KB Bunayya ICBB. Methods. This research uses a descriptive qualitative method. The data collection techniques used are observation, interviews, and documentation. The informants of this research are school principals, teachers, and administrative staff. Result. Based on the results and discussion of this research, it can be concluded that institutional management is in place at KB Bunayya ICBB. The function of institutional management is to improve the quality of education in KB Bunayya through planning, organizing, implementing, and supervising. Conclusion. KB Bunayya's institutional management strategy has supporting and inhibiting factors. The supporting factors include teachers, students, curriculum, facilities, and the community environment, while the inhibiting factors are sudden activities that make teaching less than optimal. Implementation. Developing a relevant and innovative curriculum, combined with the application of interactive learning methods, enables students to actively engage in the learning process and achieve better learning outcomes